Pengkajian Keperawatan yang Efektif bagi Gay dengan HIV/AIDS - Silalahi, Malianti (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2019)
Nursing care is a form of nurse care that can help in overcoming health problems, including those with gay / HIV / AIDS. Nursing assessment can be one of the keys to the successful implementation of nursing care. This study aims to explore effective nursing studies for gays with HIV / AIDS. This research is qualitative research with qualitative descriptive design. Data collection uses in-depth interview techniques with semi structure and uses field notes to 14 participants and is analyzed by thematic analysis. This study produced two themes, namely the focus of the assessment technique at the beginning of the meeting and the scope of the comprehensive study. Gay with HIV / AIDS takes time to establish trust and closeness with nurses. Assessment techniques at the beginning of the meeting are things that must be considered by nurses in the nursing care process. Open attitude must be considered in conducting nursing studies.